Foot-and-Mouth Disease — Epidemiology and Control - Mohapatra, J. K.; Rout, M.; Ranjan, Rajeev; Pattnaik, B. (Indian Farming, 2015)
The Foot and Mouth disease in animals is caused by a virus. Research on the disease initiated after 1930 at the IVRI after the institute had sufficient scientific staff to undertake research on this disease. This research activity was enhanced with the establishment of the All-India Coordinatd Research Project for FMD virus serotyping in 1968. The AICRP on FMD was later upgraded to full fledged Project Directorate on FMD at Mukteswar in the year 2001. Since then the PDFMD has been spearheading the FMD-related research activities in India and devising cutting-edge diagnostics for undertaking comprehensive surveillance of the disease.